2000
DOI: 10.1136/pmj.76.896.345
|View full text |Cite
|
Sign up to set email alerts
|

Status of antithyroid antibodies in Bangladesh

Abstract: To study autoimmunity among thyroid diseases, 397 thyroid patients (age 30 (13) years; M/F 75/322) from two referral centres in Bangladesh and 94 healthy controls (age 30 (13) years; M/F 24/70) were studied for antimicrosomal and antithyroglobulin antibodies. Thyroid patients were clinically grouped as suspected autoimmune thyroid disease (AITD), non-autoimmune, or indeterminate groups (where no decision could be reached). Antimicrosomal antibody was strongly positive in 19.4% and weakly positive in 7.3% of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Regarding anti thyroglobulin antibody which was also shown to be significantly higher in patients with primary hypothyroidism 74.3% than in normal population 17.1% with p<0.001 The highest percentage of positive patients in this study, were in the hypothyroid groups, which may reflect the autoimmune destruction of thyroid glands in those patients. This ratio is relatively similar when compared with research carried out by Hasanat et al (21) . This data are in accord with the study carried out by Delemeretal (22) which shows that autoimmune process by antithyroid peroxidase and antithyroglobulin antibodies were the most common cause of primary hypothyroidism.…”
Section: Discussionsupporting
confidence: 64%
“…Regarding anti thyroglobulin antibody which was also shown to be significantly higher in patients with primary hypothyroidism 74.3% than in normal population 17.1% with p<0.001 The highest percentage of positive patients in this study, were in the hypothyroid groups, which may reflect the autoimmune destruction of thyroid glands in those patients. This ratio is relatively similar when compared with research carried out by Hasanat et al (21) . This data are in accord with the study carried out by Delemeretal (22) which shows that autoimmune process by antithyroid peroxidase and antithyroglobulin antibodies were the most common cause of primary hypothyroidism.…”
Section: Discussionsupporting
confidence: 64%
“…Most of the patients with thyroid disease had detectable antithyroid antibodies. In another study, anti-TPOAbs and anti-TgAbs were found to be present in 85% and 30% to 60 % of patients with primary thyroid diseases respectively (4).…”
Section: Introductionmentioning
confidence: 89%
“…In our series 87.5% of the cases had thyroid autoantibodies positive. The series of Hasanat et al 9 and Lakshamana Rao et al 8 reported thyroid auto antibodies positivity of 63% and 83.34% respectively. In our study, in the group that was hypothyroid at presentation, thyroid autoanitibodies were positive in 66.6% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…In the euthyroid and hyperthyroid groups the thyroid antibody positivity was 100%. Hasanat et al 9 reported thyroid autoantibody positivity of 55% and 37% in their hypothyroid and hyperthyroid groups respectively.…”
Section: Discussionmentioning
confidence: 99%